METEOR: A Tool for Monitoring Behavior Preservation in Test Code Refactorings - Teixeira, Tiago Samuel Rodrigues; Silveira, Fábio Fagundes; Guerra, Eduardo Martins (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3580, 2024)
The success of test refactoring, particularly in the removal of test smells, relies on a post-refactoring evaluation to ensure that the refactored test maintains its behavior, meaning its defect detection capability. Test smells are indicative of issues within test code. While various approaches in the literature propose strategies for evaluating test behavior, they lack tool support for practical industry application. Therefore, this study introduces MeteoR, a tool model that employs a mutation testing approach to assess refactored test behavior. MeteoR is implemented as a plugin for the Eclipse IDE and is integrated with PITclipse, streamlining the collection and analysis of mutation test data for effective evaluation of test refactoring. This paper provides a detailed description of the MeteoR implementation, discusses encountered challenges and findings, and includes illustrative examples demonstrating its efficacy through a preliminary evaluation, which shows promising initial results. The video presentation of MeteoR is available at  https://doi.org/10.6084/m9.figshare.25954045 .